2017
DOI: 10.2147/opth.s120427
|View full text |Cite
|
Sign up to set email alerts
|

Refractive outcomes and safety of the implantable collamer lens in young low-to-moderate myopes

Abstract: PurposeTo evaluate visual and refractive outcomes and safety of implantable collamer lens (ICL) implantation in low-to-moderate myopia.SettingPrivate Practice – Dougherty Laser Vision, Westlake Village, CA, USA.MethodsA chart review was performed in 56 (104 eyes) consecutive patients who underwent implantation of the Visian ICL V4 model. Inclusion criteria were age between 21 and 40 years, spherical equivalent between −3.00 D and −10.00 D, and cylinder up to −5 D. Data on visual acuity, refraction, and complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 16 publications
2
30
0
2
Order By: Relevance
“…Previous studies have demonstrated that ICL V4c implantation for correcting moderate to high myopia 3 has good safety, efficacy, predictability, and stability after long-term follow-up [9][10][11] . Recently, ICL implantation has also been confirmed to perform well for low and moderate myopia [12][13] .These provide theoretical support and guidance for the use of ICL to correct residual refractive errors after corneal refractive surgery.…”
Section: Introductionmentioning
confidence: 65%
“…Previous studies have demonstrated that ICL V4c implantation for correcting moderate to high myopia 3 has good safety, efficacy, predictability, and stability after long-term follow-up [9][10][11] . Recently, ICL implantation has also been confirmed to perform well for low and moderate myopia [12][13] .These provide theoretical support and guidance for the use of ICL to correct residual refractive errors after corneal refractive surgery.…”
Section: Introductionmentioning
confidence: 65%
“…There is agreement between our results and results of Paul and Taylor who studied refractive outcomes and safety of the implantable collamer lens in young low to moderate myopes. Their study was retrospective study performed by chart review of (104 eyes) with 50 months follow up period (22). The study showed high efficacy , safety and stability of ICL during the follow up period .…”
Section: Discussionmentioning
confidence: 99%
“…Podczas ostatniej kontroli lekarskiej po operacji sferyczny ekwiwalent wynosił −0,08 ±0,01 dioptrii, a cylinder 0,29 ±0,71 dioptrii. 13 Porównanie pooperacyjnej nieskorygowanej ostrości wzroku (ang. uncorrected distance visual acuity -UCDVA) z przedoperacyjną CDVA wykazało, że 27 oczu (26%) miało lepszą pooperacyjną UCDVA i 61 oczu (59%) miało UDVA odpowiadającą przedoperacyjnej CDVA.…”
Section: Omówienieunclassified
“…Podczas ostatniego badania nie stwierdzono zmętnienia soczewki. 13 Gimbel et al przeanalizowali rezultaty wszczepienia Visian V4 ICL w oczach pacjentów krótkowzrocznych, okres obserwacji wahał się w granicach 2-14 lat. Wspomniane retrospektywne badanie wykazało, że odsetek rozwijającej się zaćmy przedniej podtorebkowej był dodatnio skorelowany z wiekiem.…”
Section: Omówienieunclassified